Taxation of Income and Economic Growth: An Empirical Analysis of 25 Rich OECD Countries - Margareta Dackehag; Åsa Hansson (Lund University, School of Economics and Management, Department of Economics, 2012)
Several empirical papers have studied the effect of government size, typically measured as government expenditures, on economic growth. There is no consensus on the direction of this impact, even though more recent studies tend to find a negative relationship between the general level of government expenditures and economic growth. This negative relationship is explained by the distortions that raising tax revenues cause on economic activities. There are, however, several ways to raise tax revenues that likely have different distortionary effects and, hence, may impact economic growth differently. This paper analyses how taxation of income influences economic growth. More precisely we study how statutory tax rates on corporate and personal income affect economic growth by using panel data from 1975 till 2010 for 25 rich OECD countries. We find that both taxation of corporate and personal income negatively influence economic growth. The correlation between corporate income taxation and economic growth is more robust, however.
Keywords: H21; H24; H25; O40; 330; Economic growth; taxation of corporate income; taxation of personal income